Circumventricular Organ Apelin Receptor Knockdown Decreases Blood Pressure and Sympathetic Drive Responses in the Spontaneously Hypertensive Rat - Griffiths, Philip R.; Lolait, Stephen J.; Paton, Julian F. R.; O’Carroll, Anne-Marie (Frontiers in Physiology, 2021)
The central site(s) mediating the cardiovascular actions of the apelin-apelin receptor (APJ) system remains a major question. We hypothesized that the sensory circumventricular organs (CVOs), interfacing between the circulation and deeper brain structures, are sites where circulating apelin acts as a signal in the central nervous system to decrease blood pressure (BP). We show that APJ gene (aplnr) expression was elevated in the CVOs of spontaneously hypertensive rats (SHRs) compared to normotensive Wistar Kyoto (WKY) controls, and that there was a greater mean arterial BP (MABP) decrease following microinjection of [Pyr1]apelin-13 to the CVOs of SHRs compared to WKY rats. Lentiviral APJ-specific-shRNA (LV-APJ-shRNA) was used to knockdown aplnr expression, both collectively in three CVOs and discretely in individual CVOs, of rats implanted with radiotelemeters to measure arterial pressure. LV-APJ-shRNA-injection decreased aplnr expression in the CVOs and abolished MABP responses to microinjection of [Pyr1]apelin-13. Chronic knockdown of aplnr in any of the CVOs, collectively or individually, did not affect basal MABP in SHR or WKY rats. Moreover, knockdown of aplnr in any of the CVOs individually did not affect the depressor response to systemic [Pyr1]apelin-13. By contrast, multiple knockdown of aplnr in the three CVOs reduced acute cardiovascular responses to peripheral [Pyr1]apelin-13 administration in SHR but not WKY rats. These results suggest that endogenous APJ activity in the CVOs has no effect on basal BP but that functional APJ in the CVOs is required for an intact cardiovascular response to peripherally administered apelin in the SHR.